Monkeypox-related knowledge and influencing factors among men who have sex with men in China: an online cross-sectional survey - Min ZHENG; Xiao-han QIAN; Zhi YUAN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo investigate monkeypox-related knowledge and influencing factors among men who have sex with men (MSM) in China. MethodsTotally 3 889 MSM aged ≥ 16 years and having anal sex in past year were recruited in 20 provincial-level administrative divisions with the assistance of community-based AIDS prevention organizations. An expert-designed electronic questionnaire on demographics, residence history, sexual behavior, and monkeypox-related knowledge was administered online among the MSM during July 1 - 3, 2022. ResultsOf the 3 563 eligible respondents averagely aged 31.0 ± 9.0 years, 72.7% (2 592) reported homosexual orientation; 53.4% (1 903) reported having sex with men in the past month; 25.7% (916) were positive for human immunodeficiency virus (HIV); 2.7% (95) reported the history of travelling to foreign countries; and 47.2% (1 681) reported the awareness about monkeypox prevention. Multivariate logistic regression analysis showed that the respondents with following characteristics were more likely to have a higher knowledge about monkeypox prevention: at elder ages (35 - 44 years vs. 16 - 24 years: odds ratio [OR] = 1.54, 95% confidence interval [95% CI]: 1.18 - 1.99, 45 - 54 years vs. 16 - 24 years: OR = 1.90, 95% CI: 1.32 - 2.74), unmarried (versus married: OR = 1.49, 95% CI: 1.15 - 1.92 ) divorced/widowed (versus married: OR = 1.56, 95% CI: 1.12 - 2.18), with the education of master and above (versus primary school and lower: OR = 1.92, 95% CI: 1.02 - 3.60), being worry about imported monkeypox epidemic in China (yes vs. no: OR = 2.68, 95% CI: 2.29 - 3.15), the history of travelling to foreign countries (yes vs. no: OR = 1.73, 95% CI: 1.13 - 2.66 ), tested positive for HIV (versus never tested: OR = 1.69, 95% CI: 1.19 - 2.40), and tested negative for HIV (versus never tested: OR = 1.79, 95% CI: 1.28 - 2.50). ConclusionThe MSM in China had paid a high attention to monkeypox epidemic, but were with a low knowledge about monkeypox epidemic prevention. The results suggest that the health education on monkeypox prevention should be strengthened among the MSM, especially among those at younger age, being married, with lower education, and never having HIV test.